2017
DOI: 10.1038/ijo.2017.236
|View full text |Cite
|
Sign up to set email alerts
|

Perirenal fat is related to carotid intima-media thickness in children

Abstract: Perirenal fat is the main abdominal fat depot associated with cIMT, especially in overweight and obese children, and may thus represent a helpful parameter for assessing CV risk in the pediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 46 publications
2
32
0
Order By: Relevance
“…Semi-automated edge detection programs have been suggested as a better approach to reduce variability in the measurement of cIMT ( 31 ). The reproducibility of measurement in the presented study was demonstrated with acceptable intra-observer variability, and well inside the limits compared to other studies ( 15 , 18 , 19 , 59 ) as it reflected the variability of actual separate measurements, contrary to off-line repetitive readings of the same image acquisition. Our study's cIMT measurement technique was fast to perform and well-tolerated in a pediatric population from 6 years of age on, and also in the adolescent age group ( 19 ).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Semi-automated edge detection programs have been suggested as a better approach to reduce variability in the measurement of cIMT ( 31 ). The reproducibility of measurement in the presented study was demonstrated with acceptable intra-observer variability, and well inside the limits compared to other studies ( 15 , 18 , 19 , 59 ) as it reflected the variability of actual separate measurements, contrary to off-line repetitive readings of the same image acquisition. Our study's cIMT measurement technique was fast to perform and well-tolerated in a pediatric population from 6 years of age on, and also in the adolescent age group ( 19 ).…”
Section: Discussionsupporting
confidence: 81%
“… Summary of the review of published data on cIMT in the pediatric population for studies reporting mean cIMT data for (A) 6–18-year age range ( 5 , 15 19 , 26 , 29 , 46 58 ), (B) under ten years ( 5 , 16 19 , 47 , 48 , 53 , 55 , 59 61 ), (C) 10–14 years ( 16 19 , 47 , 48 , 53 , 62 64 ), (D) 14–18-year age range ( 5 , 15 , 17 19 , 24 , 47 , 48 , 53 , 55 , 65 70 ). …”
Section: Resultsmentioning
confidence: 99%
“…Our study may have not excluded subjects with spurious hypertension, but we could not determine central SBP because it is an invasive measurement. cIMT was only measured on the right artery; however, we have shown consistent results regarding the association of cIMT with CV risk in a number of manuscripts 39,40 . No external validations for the ultrasound measurements were performed; however, cIMT and renal size have been shown to be easily and reproducibly measured by ultrasound in numerous studies 41,42 .…”
Section: Discussionsupporting
confidence: 65%
“…Serum endocrine-metabolic parameters were measured using automated tests, as described before [23]. Serum glucose was measured by the hexokinase method.…”
Section: Methodsmentioning
confidence: 99%